Normal T and B Cell Responses Against SARS-CoV-2 in a Family With a Non-Functional Vitamin D Receptor: A Case Report - Kongsbak-Wismann, Martin; Al-Jaberi, Fatima A. H.; Schmidt, Jonas Damgård; Ghanizada, Mustafa; Hansen, Cecilie Bo; Lopez, Daniel Villalba; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte Menné; Stryhn, Anette; Garred, Peter; Buus, Søren; et al. (Frontiers in Immunology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has severely impacted daily life all over the world. Any measures to slow down the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and to decrease disease severity are highly requested. Recent studies have reported inverse correlations between plasma levels of vitamin D and susceptibility to SARS-CoV-2 infection and COVID-19 severity. Therefore, it has been proposed to supplement the general population with vitamin D to reduce the impact of COVID-19. However, by studying the course of COVID-19 and the immune response against SARS-CoV-2 in a family with a mutated, non-functional vitamin D receptor, we here demonstrate that vitamin D signaling was dispensable for mounting an efficient adaptive immune response against SARS-CoV-2 in this family. Although these observations might not directly be transferred to the general population, they question a central role of vitamin D in the generation of adaptive immunity against SARS-CoV-2.